The Urgency of The Principle of Interest In Insurance Agreements - Mariyam, Siti (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: This article explores insurance agreements as distinct contracts that facilitate the transfer of risk from the insured to the insurer. It delves into the critical factors ensuring the validity and sustainability of such agreements, emphasizing the role of legal principles in maintaining fairness and stability within the insurance framework.Purposes of the Research: The study aims to evaluate the urgency of the principle of interest in insurance agreements through a thorough literature review and juridical analysis. It examines how this principle prevents unethical practices like speculation, gambling, and fraud, ensuring that insurance contracts remain equitable and aligned with legal and ethical standards.Methods of the Research: The research employs a qualitative approach, combining a comprehensive literature review with juridical analysis. It examines legal texts, case studies, and scholarly articles to assess the application of the principle of interest in insurance agreements, focusing on its legal implications and practical effectiveness in the insurance industry.Results Main Findings of the Research: The findings highlight that the principle of interest serves a dual purpose: protecting insurers from fraudulent claims while fostering trust and integrity across the insurance system. This principle ensures that only legitimate interests are insured, promoting fairness and reducing systemic risks, thus enhancing confidence in insurance as a reliable risk management mechanism.